Dissipation of earthward propagating flux rope through rereconnection with geomagnetic field: An MMS case study - Poh,G; Slavin,JA; Lu,S; Le,G; Ozturk,DS; Sun,W; Zou,S; Eastwood,JP; Nakamura,R; Baumjohann,W; Russell,CT; Gershman,DJ; et al. (Journal of Geophysical Research: Space Physics, 2019)
Threedimensional global hybrid simulations and observations have shown that earthwardmoving flux ropes (FRs) can undergo magnetic reconnection (or rereconnection) with the nearEarth dipole field to create dipolarization front (DF)like signatures that are immediately preceded by brief intervals of negative BZ. The simultaneous erosion of the southward BZ field at the leading edge of the FR and continuous reconnection of lobe magnetic flux at the Xline tailward of the FR result in the asymmetric southnorth BZ signature in many earthwardmoving FRs and possibly DFs with negative BZ dips prior to their observation. In this study, we analyzed Magnetospheric MultiScale (MMS) observation of fields and plasma signatures associated with the encounter of an ion diffusion region ahead of an earthwardmoving FR on 3 August 2017. The signatures of this rereconnection event were (i) +/− BZ reversal, (ii) −/+ bipolartype quadrupolar Hall magnetic fields, (iii) northward superAlfvénic electron outflow jet of ~1,000–1,500 km/s, (iv) Hall electric field of ~15 mV/m, (v) intense currents of ~40–100 nA/m2, and (vi) J·E′ ~0.11 nW/m3. Our analysis suggests that the MMS spacecraft encounters the ion and electron diffusion regions but misses the Xline. Our results are in good agreement with particleincell simulations of Lu et al. (2016, https://doi.org/10.1002/2016JA022815). We computed a dimensionless reconnection rate of ~0.09 for this rereconnection event and through modeling, estimating that the FR would fully dissipate by −16.58 RE. We demonstrated pertubations in the highlatitude ionospheric currents at the same time of the dissipation of earthwardmoving FRs using ground and spacebased measurements.